Mitochondrial Reactive Oxygen Species Are Essential for the Development of Psoriatic Inflammation - Mizuguchi, Soichi; Gotoh, Kazuhito; Nakashima, Yuya; Setoyama, Daiki; Takata, Yurie; Ohga, Shouichi; Kang, Dongchon (Frontiers in Immunology, 2021)
Psoriasis is a common immune-mediated, chronic, inflammatory skin disease that affects approximately 2–3% of the population worldwide. Although there is increasing evidence regarding the essential roles of the interleukin (IL)-23/IL-17 axis and dendritic cell (DC)-T cell crosstalk in the development of skin inflammation, the contributions of mitochondrial function to psoriasis are unclear. In a mouse model of imiquimod (IMQ)-induced psoriasiform skin inflammation, we found that hematopoietic cell-specific genetic deletion of p32/C1qbp, a regulator of mitochondrial protein synthesis and metabolism, protects mice from IMQ-induced psoriatic inflammation. Additionally, we demonstrate that p32/C1qbp is an important regulator of IMQ-induced DC activation, both in vivo and in vitro. We also found that p32/C1qbp-deficient DCs exhibited impaired production of IL-1b, IL-23, and mitochondrial reactive oxygen species (mtROS) after IMQ stimulation. Because the inhibition of mtROS suppressed IMQ-induced DC activation and psoriatic inflammation, we presume that p32/C1qbp and mtROS can serve as therapeutic targets in psoriasis.